2004
DOI: 10.1081/cbi-200025989
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Discrimination and Transient Mood Change in Young Men and Women: Variation by Season, Mood State, and Time of Day

Abstract: Odor performance varies by clinical state and gender, though little is known about its variation by season or time of day. Many odors, including lavender, induce transient mood changes. This study explored discrimination differences between various lavender oil blends and their effects on transient mood in the morning and evening in depressed and nondepressed adults. We also determined seasonal influences on these measures. A total of 169 subjects, 98 women and 71 men (mean age +/- SD, 19.3 +/- 1.6 y) particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 144 publications
(211 reference statements)
4
26
0
Order By: Relevance
“…43 Two studies addressed possible relationship between depressive symptoms and olfactory function in non-clinical young adults. 44,45 In both studies, no association was found between olfactory discrimination and depressive symptoms assessed with the BDI. In one of these studies some correlation was observed between the BDI scores and olfactory thresholds measured with the Sniffin Sticks.…”
Section: Discussionmentioning
confidence: 89%
“…43 Two studies addressed possible relationship between depressive symptoms and olfactory function in non-clinical young adults. 44,45 In both studies, no association was found between olfactory discrimination and depressive symptoms assessed with the BDI. In one of these studies some correlation was observed between the BDI scores and olfactory thresholds measured with the Sniffin Sticks.…”
Section: Discussionmentioning
confidence: 89%
“…Olfactory discrimination scores were assessed in young adults (mean age: 19.3 ± 1.6) by Goel and Grasso (2004). The olfactory discrimination test included 7 items and was based on five different blends of commercially available lavender oil.…”
Section: Findings On Olfactory Function In Depressionmentioning
confidence: 99%
“…As olfactory functions have been repeatedly reported to decline with age (e.g., Doty et al, 1984a; Hummel et al, 2007), in these two studies, effects of age might have overshadowed effects of depression, resulting in overall low olfactory performances, which are unlikely to be further reduced by psychiatric symptoms. In addition, one study (Goel and Grasso, 2004) indicated that olfactory discrimination performance for certain odors might even be increased during depressive mood states.…”
Section: Findings On Olfactory Function In Depressionmentioning
confidence: 99%
“…[39] According to several researches, odors can modulate cognition,[10] mood,[11] and behavior. [12] There is a powerful connection between odors and memories, especially those from the distant past, charged with emotional significance due to major anatomical connections existing between brain structures such as the hypothalamus and limbic system which are involved in emotion and memory.…”
Section: Introductionmentioning
confidence: 99%